2018
DOI: 10.1155/2018/8629894
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Drilling Parameters Using Grey Relational Analysis and Response Surface Methodology of Biaxial Glass Fibre Reinforced with Modified Epoxy Resin Composite

Abstract: This research work attempts to study the most prominent factor of the drilling operations performed on different thicknesses of biaxial glass fibre reinforced with graphene platelet nanopowder and epoxy composite using three different drills. Damages are induced in the workpieces to analyse the effect of changed cutting parameters and different tool materials for varied thicknesses of the plates during the drilling process. The resultant drilled hole exhibited surface irregularities that are measured using SUR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…14 An investigation on the impact of various glass fiber/graphene/epoxy composite thicknesses on drilling performance was studied. 15 It was reported that lower thickness (2 mm) of composite had excellent performance for high-speed steel (HSS) drill at higher speed and lower feed rate. The effect of various drilling parameters such as feed rate and speed on delamination and tool wear for 6 mm thick of GFRP composite was examined.…”
Section: Introductionmentioning
confidence: 99%
“…14 An investigation on the impact of various glass fiber/graphene/epoxy composite thicknesses on drilling performance was studied. 15 It was reported that lower thickness (2 mm) of composite had excellent performance for high-speed steel (HSS) drill at higher speed and lower feed rate. The effect of various drilling parameters such as feed rate and speed on delamination and tool wear for 6 mm thick of GFRP composite was examined.…”
Section: Introductionmentioning
confidence: 99%
“…It indicates the uncertainty in the measured ap proximation values. In a recent study, the error bar was an informative tool to show the goodness of fit or dispersion of the data set [55,56]. In detail, statistical testing such as hypothesis testing, confidence interval and ttest should be performed to draw the final conclusion.…”
Section: Materials Selection Based On Performance Of Mechanical Propermentioning
confidence: 99%
“…Gray Relational Analysis, more commonly abbreviated as GRA, is one of the Multi-Criteria Decision Making (MCDM) approaches that is one of the most widely used for the resolution of multi-criteria problems. The GRA was selected as the methodology to explore the various outcomes, and the findings demonstrated that it was an effective strategy [22][23][24]. Although the GRA has many beneficial elements, the performance characteristics are not well understood, and there is a significant degree of uncertainty regarding the method that the GRA takes.…”
Section: Introductionmentioning
confidence: 99%